Effect of temperature and storage on the germination of cucumis melo L. after accelerated ageing - Elizabeth, Ngitar @ Lugom. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
A study was conducted to evaluate the effects of short period of accelerated ageing on storage and germination of Cucumis melo.L seeds. After seeds were placed in dessicators to age for 5 days at 40 -42°C and 100% relative humidity, they were put in air -tight bottles, and stored in refrigerator (3-5°C), ambient room (28-30°C) and cold room (-12°C) for one week, and evaluated. Accelerated ageing caused a marked decreased in germination of C. melD seeds in 4 days and poor seedling growth after one week of storage. The detrimental period of germination for C. melD was at 1134.01 hours, which are 47 days and 6 hours after accelerated ageing and 619.77 hours (25 days and 19 hours) when seeds are stored following ageing. Hence, the ideal storage condition for storing C. melD was the refrigerator with 3-5°C and a cool environment of 40-50% relative humidity.